1994
DOI: 10.3109/00016349409006268
|View full text |Cite
|
Sign up to set email alerts
|

Placental hstology and fetal blood flow in intrauterine growth retardation

Abstract: Placental infarction would seem to be a valuable morphological marker of uteroplacental vascular disease related to IUGR and impaired fetal and umbilical blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 18 publications
4
33
0
1
Order By: Relevance
“…In agreement with our previous studies [11,13], we have found a strong association between the Doppler findings indicating high resistance to arterial flow on both sides of placenta (BFC I-III and UAS 3-4) and placental ischemic changes expressed as the presence of infarctions and high ischemic score (Table III). The increased inflammatory response that characterises both placental ischemic changes and deciduitis can have contributed to these hemodynamic changes.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with our previous studies [11,13], we have found a strong association between the Doppler findings indicating high resistance to arterial flow on both sides of placenta (BFC I-III and UAS 3-4) and placental ischemic changes expressed as the presence of infarctions and high ischemic score (Table III). The increased inflammatory response that characterises both placental ischemic changes and deciduitis can have contributed to these hemodynamic changes.…”
Section: Discussionsupporting
confidence: 80%
“…It is usually of no significance unless it affects more than 10-20% of the placental volume (11). The existence of a relation between fetal hypoxia and placental infarction has been shown (12). In the present study, placental infarction was detected in 58% and 62%, 4% of group I, group II and group III, respectively.…”
Section: Discussionmentioning
confidence: 47%
“…The aim of the study was to quantitate the extent of pontosubicular apoptosis in the 17 cases and document any apoptosis in the cerebral cortex as well, using both standard histology and stains specific for apoptosis. Placental infarction is a morphological marker of uteroplacental insufficiency in pregnancies complicated by IUGR [17]. IUGR associated with abnormal blood flow in the umbilical artery is associated with chronic fetal hypoxaemia [23].…”
Section: Introductionmentioning
confidence: 99%